Abstract CMPD2 Braumann+Filipe - Braumann, Carlos A. (2008)
Scientific meeting: II Conference on Computational and Mathematical Population Dynamics (DESTOBIO 4 + MPD 8), Campinas, Brazil, July 16-20. Oral communication on stochastic differential equation models for individual animal growth (from birth to maturity).